Description of the first sleeping sickness case diagnosed in Burkina Faso since two decades. - Emilie Dama; Aboubacar Drabo; Jacques Kaboré; Elie Ouédraogo; Bamoro Coulibaly; Hamidou Ilboudo; Justin Kaboré; Charlie Franck Compaoré; Hassane Sakandé; Micheline Ouédraogo; Jean-Baptiste Rayaissé; Fabrice Courtin; et al. (Public Library of Science (PLoS), 2018)
Burkina Faso belongs to a group of countries in which human African trypanosomiasis (HAT), caused by Trypanosoma brucei gambiense, is no longer considered to be a public health problem. Although no native cases have been detected since 1993, there is still the risk of HAT re-emergence due to significant population movements between Burkina Faso and active HAT foci in Côte d'Ivoire. Since 2014, Burkina Faso receives support from the WHO to implement a passive surveillance program. This resulted in the detection in 2015 of the first putative native HAT case since two decades. However, epidemiological entomological and molecular biology investigations have not been able to identify with certainty the origin of this infection or to confirm that it was due to T. b. gambiense. This case emphasises the need to strengthen passive surveillance of the disease for sustained elimination of HAT as a public health problem in Burkina Faso.